Auditoría de gestión a los departamentos financiero y de ventas de la empresa Ecolac Cía. Ltda., de la ciudad de Loja, período 2020. - Piedra Ortega, Karen Ivanova (2024)
The curricular integration work entitled, "MANAGEMENT AUDIT, TO THE FINANCIAL AND SALES MANAGEMENT OF THE COMPANY ECOLAC CIA LTDA, OF THE CITY OF LOJA PERIOD 2020", was developed with the purpose of evaluating the internal control system and through the application of management indicators to measure the degree of efficiency, effectiveness, and economy with which they perform their activities, in order to formulate conclusions and recommendations to improve business management. In addition, it fulfills a prerequisite to obtain the degree and title of Bachelor in Accounting and Auditing. In order to meet the objectives, research methods and the management audit process were used to gather information, starting with the preparation of the work order, initial notification, mark sheet, index sheet, time and work distribution sheet. It begins with Phase I Preliminary Knowledge where the previous visit to the facilities of the company Ecolac Cía. Ltda. was made, collecting the necessary information and documentation for the development of the management audit. In phase II Planning, the planning memorandum and the audit risk matrix were prepared, and the components to be audited, which are the financial level and the sales level, were determined. In phase III Execution, based on the procedures proposed in the audit programs, the internal control system of each of the components audited was evaluated to establish the level of risk and confidence in the operations performed and whether there is compliance with the legal framework in force, obtaining as a product significant findings, which were detailed in the narrative cards with the respective evidence. In addition, management indicators were applied to determine the degree of efficiency, effectiveness and economy in the administration and use of resources. In Phase IV Communication of Results, a final report was issued containing the general and specific results of each of the components examined; and finally, in Phase V Follow-up, a timetable was established for compliance with the recommendations. At the end of the management audit in the company Ecolac Cía. Ltda. The conclusions and recommendations are presented according to each proposed objective, which are included in the final report as a contribution to decision-making.